AKR1C2 silencing promotes ferroptosis and inhibits proliferation, migration, and invasion in lung cancer cells - Yi Cui; Zhihui Liu (PLoS ONE, 2025)
Background Lung cancer is the leading cause of cancer-related deaths worldwide, so research and development of potential therapeutic targets is urgent. Methods The target gene, AKR1C2, was screened using the TCGA and FerrDb databases. The expression of AKR1C2 in lung cancer, its correlation with the clinical characteristics of patients, and the biological roles and molecular mechanisms involved were assessed by bioinformatics. The expression levels of AKR1C2 in normal lung epithelial cells and lung cancer cells were compared by qRT-PCR and Western blot. The effects of AKR1C2 knockdown on the malignant phenotype of lung cancer cells were evaluated using Transwell, wound healing, and CCK8 assays. Finally, the impact of silencing AKR1C2 on malondialdehyde, reactive oxygen species, Fe2+ levels, and ferroptosis-related genes in lung cancer cells were experimentally investigated. Results AKR1C2 is highly expressed in lung adenocarcinoma tissues, and the expression level correlates with patient gender, tumor stage, lymph node metastasis, and prognosis. AKR1C2 is associated with substance metabolism, steroid hormone biosynthesis, cellular lipid metabolism, and oxidoreductase activity. AKR1C2 had high expression levels in A549 cells. AKR1C2 silencing inhibited cell viability, invasion, and migration. In A549 cells, AKR1C2 knockdown markedly raised the levels of reactive oxygen species, malondialdehyde, and Fe²⁺. The knockdown of AKR1C2 regulated the expression of ferroptosis-related genes. Conclusion Our study demonstrates that AKR1C2 knockdown promotes ferroptosis and inhibits malignant biological behaviors in lung cancer cells.